Sources of stress in online learning scale: development and validation of an instrument to evaluate students’ stressors associated with the online learning - Topală, Ioana-Roxana; Necșoi, Daniela-Veronica; Cazan, Ana-Maria; Stan, Maria-Magdalena (Frontiers in Psychology, 2025)
IntroductionSince transitioning to online teaching and learning was forced to happen in the shortest ever time span during the COVID-19 pandemic, the opportunity arose for educational researchers to reflect on tools and means for measuring and explaining students’ and teachers’ relevant experiences related to the change. One of our responses to this challenge was to elaborate, administer and evaluate the psychometric properties of an instrument – Sources of Stress in Online Learning Scale (SSOLS) - that would help educational professionals assess students ‘perceptions upon sources of stress regarding their online learning. Furthermore, SSOLS’s factors would allow educators to predict students’ learning engagement due to the valid predictive association.MethodsThe present research aimed to develop and test an instrument assessing the sources of stress in the context of academic online learning and to articulate its psychometric properties. The study focused on the responses of more than 500 university students regarding perceived stressors pertaining to the experience of online learning.ResultsOur analysis demonstrated that the instrument (SSOLS) is reliable and valid in measuring the sources of stress associated with online learning. Also, the dimensions of SSOLS were shown to be valid predictors for academic engagement.DiscussionThe significance of this study lies also in its contribution to both theoretical understanding and practical applications regarding academic stress in online learning environments.